2019
DOI: 10.3390/cancers11121914
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Lymph Node Ratio in Advanced Gastric Cancer After Neoadjuvant Chemotherapy

Abstract: The ratio of positive lymph nodes (LNs) to the total LN harvest is called the LN ratio (LNR). It is an independent prognostic factor in gastric cancer (GC). The aim of the current study was to evaluate the impact of neoadjuvant chemotherapy (NAC) on the LNR (ypLNR) in patients with advanced GC. We retrospectively analyzed the data of patients with advanced GC, who underwent gastrectomy with N1 and N2 (D2) lymphadenectomy between August 2011 and January 2019 in the Department of Surgical Oncology at the Medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…• staging laparoscopy should be maintained, with informed consent to proceed to gastrectomy if the primary tumor is resectable ○ especially in non-intestinal tumors 45 • for early GC following non-radical endoscopic resection (R1), the definitive radical surgery may be postponed • neoadjuvant (radio-)chemotherapy for resectable cases deferred • upfront gastrectomy preferred if easy resectable with low risk of respiratory complications ○ major GC surgery, as recently defined by experts, 46 only in referral centers with proven low morbidity/ mortality rates, performed by experienced surgeons or under their strict supervision 47 ○ option: HIPEC for limited peritoneal dissemination (CY1; PCI<7; P1/2) should be deferred • adjuvant chemotherapy reserved only for patients with lymph node pN-positive tumors 48 • for bleeding GC, endoscopic management is the first choice option, followed by radiotherapy, and urgent gastrectomy reserved only for life-threatening hemorrhage • perforation of GC with peritonitis should be treated minimally-invasive, with peritoneal lavage and drainage, after no improvement with intravenous broadspectrum antibiotic therapy • for non-resectable or borderline resectable tumors with high risk of complications, primary radical radiochemotherapy should be proposed ○ cases with clinical response might be re-evaluated for resectability in the post-pandemic time ○ otherwise (no tumor/lymph node regression) this radiotherapy should be regarded as definitive treatment • all other loco-regionally advanced (cT4 or cN3) and metastatic (M1; including CY1 or P1-3 following staging laparoscopy) cases should be treated with palliative chemotherapy if performance status is good ○ conversion therapy (surgical resectability reevaluation) postponed to the post-pandemic era 49 Emergency presentation of GC is uncommon, usually associated with an advanced stage and lower rates of operability. The necessity to perform an emergency operation within 24 hours is exceedingly rare.…”
Section: Strategy For the Treatment Of Gc During The Covid-19 Pandemicmentioning
confidence: 99%
“…• staging laparoscopy should be maintained, with informed consent to proceed to gastrectomy if the primary tumor is resectable ○ especially in non-intestinal tumors 45 • for early GC following non-radical endoscopic resection (R1), the definitive radical surgery may be postponed • neoadjuvant (radio-)chemotherapy for resectable cases deferred • upfront gastrectomy preferred if easy resectable with low risk of respiratory complications ○ major GC surgery, as recently defined by experts, 46 only in referral centers with proven low morbidity/ mortality rates, performed by experienced surgeons or under their strict supervision 47 ○ option: HIPEC for limited peritoneal dissemination (CY1; PCI<7; P1/2) should be deferred • adjuvant chemotherapy reserved only for patients with lymph node pN-positive tumors 48 • for bleeding GC, endoscopic management is the first choice option, followed by radiotherapy, and urgent gastrectomy reserved only for life-threatening hemorrhage • perforation of GC with peritonitis should be treated minimally-invasive, with peritoneal lavage and drainage, after no improvement with intravenous broadspectrum antibiotic therapy • for non-resectable or borderline resectable tumors with high risk of complications, primary radical radiochemotherapy should be proposed ○ cases with clinical response might be re-evaluated for resectability in the post-pandemic time ○ otherwise (no tumor/lymph node regression) this radiotherapy should be regarded as definitive treatment • all other loco-regionally advanced (cT4 or cN3) and metastatic (M1; including CY1 or P1-3 following staging laparoscopy) cases should be treated with palliative chemotherapy if performance status is good ○ conversion therapy (surgical resectability reevaluation) postponed to the post-pandemic era 49 Emergency presentation of GC is uncommon, usually associated with an advanced stage and lower rates of operability. The necessity to perform an emergency operation within 24 hours is exceedingly rare.…”
Section: Strategy For the Treatment Of Gc During The Covid-19 Pandemicmentioning
confidence: 99%
“…However, the predictive value of LNR in patients receiving neoadjuvant chemotherapy has not been reported. Recently, it was reported that LNR was associated with tumor diameter, Lauren classification, and tumor regression grade (TRG) [ 9 ]. Our results showed that LNR remained an independent prognostic factor for gastric cancer patients after neoadjuvant chemotherapy in both the proposal and validation cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, LNR showed a better prognostic value than the N stage [ 7 8 ]. However, few studies have investigated the prognostic value of LNR in patients with gastric cancer after preoperative chemotherapy [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The clinicopathological factors that predict prognosis have been discussed in several studies, and histological response and ypTNM stage after neoadjuvant therapy are generally considered effective predictors (15)(16)(17)(18)(19)(20)(21)(22)(23)..Yukinori compared the prognostic value of evaluation criteria, the Response Evaluation Criteria in Solid Tumors (RECIST) standard, the Japanese Classification of Gastric Cancer (JCGC) standard and the histological response. A total of 100 patients were included in the JCOG0210 and JCOG0405 studies.…”
Section: Discussionmentioning
confidence: 99%